ANALYSIS OF FRACTIONAL ORDER PIλDμ POWER CONTROL OF A NUCLEAR REACTOR - Puchalski, Bartosz; Duzinkiewicz, Kazimierz; Rutkowski, Tomasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
In this paper, the synthesis of fractional –order PIλDμ power controller for the PWR (Pressurized Water Reactor) nuclear reactor is presented. For this purpose the point kinetics and heat transfer nonlinear model of the PWR nuclear reactor with thermal feedback mechanisms from lumped fuel and coolant temperature was used. The parameters of the fractional-order PIλDμ controller were tuned due to optimization of the standard integral performance indexes determined on the basis of the step response. Firstly – the typical second order oscillatory dynamic system and secondly – the linear PWR nuclear reactor model derived from nonlinear model was used to show that the fractional order PIλDμ controller may become a alternative to standard PID controller.